Hologene 5: A Phase II/III Clinical Trial of Combined Cell and Gene Therapy of Junctional Epidermolysis Bullosa - De Rosa, Laura; Enzo, Elena; Zardi, Giulia; Bodemer, Christine; Magnoni, Cristina; Schneider, Holm; De Luca, Michele (Frontiers in Genetics, 2021)
Epidermolysis bullosa (EB) refers to a group of devastating genetic diseases characterized by skin and mucosal fragility and formation of blisters, which develop either spontaneously or in response to minor mechanical trauma. There is no definitive therapy for any form of EB. Intermediate junctional EB (JEB) caused by mutations in the gene LAMB3 has been the first genetic skin disease successfully tackled by ex vivo gene therapy. Here we present a multicenter, open-label, uncontrolled phase II/III study that aims at confirming the efficacy of Hologene 5, a graft consisting of cultured transgenic keratinocytes and epidermal stem cells and meant to combine cell and gene therapy for the treatment of LAMB3-related JEB. Autologous clonogenic keratinocytes will be isolated from patients’ skin biopsies, genetically corrected with a gamma-retroviral vector (RV) carrying the full-length human LAMB3 cDNA and plated onto a fibrin support (144 cm2). The transgenic epidermis will be transplanted onto surgically prepared selected skin areas of at least 6 JEB patients (4 pediatric and 2 adults). Evaluation of clinical efficacy will include, as primary endpoint, a combination of clinical parameters, such as percentage of re-epithelialization, cellular, molecular and functional parameters, mechanical stress tests, and patient-reported outcome, up to 12 months after transplantation. Safety and additional efficacy endpoints will also be assessed during the clinical trial and for additional 15 years in an interventional non-pharmacological follow-up study. If successful, this clinical trial will offer a therapeutic option for skin lesions of JEB patients with LAMB3 mutations and pave the way for a combined cell and gene therapy platform tackling other forms of EB and different genodermatoses. The clinical study protocol is identified by the EUDRACT number 2018-000261-36.